Ultrasound Guided Cervical Plexus Block for Parathyroidectomy-Out First Experiences - Stojanovic, Marina; Toskovic, Anka; Mojsic, Irena; Jovanovic, Milan; Zoric, Goran; Odalovic, Bozidar; Slijepcevic, Nikola; Tausanovic, Katarina; Rovcanin, Branisalv; Buzejic, Matija; Vucen, Duska; Stepanovic, Boban; et al. (International Journal of Innovative Research in Medical Science, 2023)
Ultrasound guided Cervical Plexus Block (CPB) is a technique that has been applied in parathyroid surgery. Main advantages of ultrasound technique include a direct view of nerves; local anaesthetic (LA) spreading during injection; reduced volume of LA; blood vessels and other structures injury is significantly reduced. It is especially useful in patients with serious comorbidities, in which possible peri-operative consequences and risks of general anaesthesia can be avoided. Based on our first results of the presented cases, we can say that superficial CPB is a safe and simple procedure in order to provide perioperative analgesia in parathyroid surgery.